Meeting 24-hour movement guidelines and the relationship with active commuting to school in Spanish urban areas - Martín-Moraleda, Evelyn; Pinilla-Quintana, Iván; Romero-Blanco, Cristina; Hernández-Martínez, Antonio; Jiménez-Zazo, Fabio; Dorado-Suárez, Alberto; García-Coll, Virginia; Cabanillas-Cruz, Esther; Martínez-Romero, María Teresa; Herrador-Colmenero, Manuel; Queralt, Ana; Castro-Lemus, Nuria; et al. (Frontiers in Sports and Active Living, 2025)
IntroductionNew guidelines from Canada indicate that the integration of all movement behaviours [physical activity (PA), screen time (ST) and sleep time (SLT)] is important for health across the day. Active commuting to school (ACS) provides an opportunity to increase PA levels daily while replacing sedentary time passively commuting. The aim of this study was to assess the prevalence of ACS, and if meeting the different guidelines included in the 24-Hour Movement Guidelines is associated with ACS in adolescents.MethodsA cross-sectional study was conducted to investigate adherence to ACS in relation to environment, psychosocial variables, and healthy lifestyle factors in Spanish adolescents. The final sample included 686 adolescents (mean age = 14.81 ± 0.52 years, 50.8% girls) from seven Spanish urban areas stratified by SES and walkability. Adolescents filled in an “ad hoc” questionnaire on the mode of commuting to school and lifestyle behaviors based on the PACO&PACA questionnaire. Logistic regression models were fit to evaluate if meeting the 24-Hour Movement Guidelines was associated with ACS. The level of significance was set at p ≤ 0.05.ResultsA total of 55.8% adolescents commuted actively from home to school. Data showed active commuters (AC) met 24-Hour Movement Guidelines more than passive commuters (PC). Evidence from the binary logistic regression indicated that those who met two Guidelines (aOR = 1.62; 95% CI: 1.01–2.59; p = 0.047) had higher odds of ACS than those who did not meet any 24-Hour Movement Guidelines. In particular, girls who met two or all 24-Hour Movement Guidelines had higher odds of ACS than those who met none (OR = 2.06, 95% CI: 1.10–3.87; OR = 2.30, 95% CI: 1.00–5.27, respectively).ConclusionsIn conclusion, our study suggests that meeting more 24-Hour Movement Guidelines is associated with ACS in adolescents. In addition, promoting ACS as a strategy to meet the 24-Hour Movement Guidelines is recommended particularly for adolescent girls.